Pentingnya Pengetahuan Kontrasepsi Darurat dan Permasalahannya dimasa Pandemi Covid-19 di Wilayah Kerja Maccini Sawah - Ekayanti Hafidah Ahmad; Nurbaiti Nurbaiti; Erna Kasim; Nurhayati Nurhayati; Sunita Sri Wahyuni; Muh. Irfan (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2021)
The Covid 19 pandemic has an impact on family planning (KB) programs. The policy issued by the government is to suppress the transmission of this virus by providing online family planning services. Apart from that, PUS (Couples of Childbearing Age) is recommended to delay pregnancy. However, if this policy is not followed with appropriate use of contraceptives and there is a decline in family planning participation, there will be a surge in population. Therefore, nurses as educators have a responsibility to provide education so that the level of knowledge about family planning increases. This community service aims to increase the knowledge of Women of Childbearing Age (WUS) regarding family planning and the appropriate use of contraceptives during the Covid 19 pandemic. The method used is to provide intervention in the form of health education about family planning via a zoom meeting link with power point media to 40 WUS. person. To determine differences in knowledge levels, a pretest and posttest were carried out using a questionnaire. The community service results show that the average score before the KB health program is 58 (poor) and the average score after the health education program is 88 (good). The use of contraceptives before health care was carried out, namely 17 people (44%) did not use contraceptives. The majority of WUS who use contraception use hormonal contraception, namely 8 people (35%) out of 23 WUS. Health education during community service activities during the Covid 19 pandemic was able to increase WUS' knowledge about family planning, but WUS were not able to decide on the appropriate use of contraception because they had to discuss it with their husband/partner.